Optimal design of water pipeline networks for the development of shale gas resources. Issue 1 (2nd October 2020) - Cafaro, Diego C.; Grossmann, Ignacio
Abstract: One of the major concerns in shale gas production is water management. Millions of gallons of water are injected to fracture each well and a significant amount returns to the surface as flowback. Operators are increasingly reusing flowback to reduce freshwater consumption and impaired water disposal. Because of this, networks of water pipelines in U.S. shales are growing fast. This work is aimed at addressing the optimal planning of shale gas operations in multiple wellpads together with the design of water distribution networks (WDN). We propose a multiperiod mixed‐integer linear programming model to solve the challenging stay‐or‐mobilize trade‐off. The proposed model permits to schedule operations at a detailed level, accounting for the WDN required to maximize the reuse of impaired water. We present illustrative examples involving up to 20 pads, 4 frac‐crews, and 100 wells developed over 1 year, showing that the design of the WDN can be effectively optimized.